A Novel Role of A2AR in the Maintenance of Intestinal Barrier Function of Enteric Glia from Hypoxia-Induced Injury by Combining with mGluR5 - Sun, Lihua; Li, Xiang; Guan, Haidi; Chen, Shuaishuai; Fan, Xin; Zhou, Chao; Yang, Hua; Xiao, Weidong (Frontiers in Pharmacology, 2021)
During acute intestinal ischemia reperfusion (IR) injury, the function of intestinal epithelial barrier (IEB) are often disrupted. Enteric glial cells (EGCs) play an important role in maintaining the integrity of IEB functions. However, the mechanism of EGCs in the regulation of IEB functions under IR stimulation is unknown. Here, the present study revealed that adenosine A2A receptor (A2AR) is one important protein in mediating the barrier-modulating roles of EGCs. A2AR knockout displayed more serious intestinal injury in the A2AR KO mice than WT mice after IR stimulation, accompanied with the significant increase of A2AR expression in response to IR challenge. To further investigate the role of A2AR in IEB, an in vitro EGC-Caco-2 co-culture system was established. Hypoxia stimulation were used to mimic the process of in vivo IR. We found that the addition of A2AR agonist CGS21680 in EGCs attenuated the hypoxia-induced intestinal epithelium damage through up-regulating ZO-1 protein expression of cocultured Caco-2 monolyers. Furthermore, we showed thatA2AR and metabotropic glutamate receptor 5 (mGluR5) combined to activate the PKCα-dependent pathway in hypoxia condition. In summary, our results first time reveal that hypoxia induce the A2AR-mGluR5 interaction in EGCs to protect IEB function via PKCα pathway.